Market institutions in Sub-Saharan Africa : theory and evidence - Fafchamps, Marcel (Comparative institutional analysis, 2004)
An analysis of recent data on the economic behavior of market institutions in sub-Saharan Africa, with implications for future research and current policy. In Market Institutions in Sub-Saharan Africa, Marcel Fafchamps synthesizes the results of recent surveys of indigenous market institutions in twelve countries, including Benin, Ghana, Kenya, Madagascar, Malawi, and Zimbabwe, and presents findings about economics exchange in Africa that have implications both for future research and current policy. Employing empirical data as well as theoretical models that clarify the data, Fafchamps takes as his unifying principle the difficulties of contract enforcement. Arguing that in an unpredictable world contracts are not always likely to be respected, he shows that contract agreements in sub-Saharan Africa are affected by the absence of large hierarchies (both corporate and governmental) and as a result must depend to a greater degree than in more developed economies on social networks and personal trust. Fafchamps considers policy recommendations as they apply to countries in three different stages of development: countries with undeveloped market institutions, like Ghana; countries at an intermediate stage, like Kenya; and countries with developed market institutions, like Zimbabwe. Market Institutions in Sub-Saharan Africa caps ten years of personal research by the author. Fafchamps, in collaboration with such institutions as the Africa Division of the World Bank and the International Food Policy Research Institute, participated in the surveys of manufacturing firms and agricultural traders that provide the empirical basis for the book. The result is a work that makes a significant contribution to research on the continuing economic stagnation of many countries in sub-Saharan Africa and is also largely accessible to researchers in other fields and policy professionals.